PENGKAJIAN USAHATANI PADI GOGO DI KABUPATEN PANDEGLANG - Purba, Resmayeti (Jurnal Agroekoteknologi, 2015)
Development of upland rice is one of the answers in increasing rice production, but the productivity of upland rice in Banten is still very low. One reason is the low use of improved varieties. But of the many  upland rice varieties are not all suitable to be developed in a region. To  find suitable varieties are developed in a region need to be  an assessment of the introduction of varieties to obtain location-specific adaptive varieties. Assessments conducted in Cisehreheun Village, Cigeulis Sub district, Pandeglang District, during  June-September 2013. Assessments using a  randomized block design with upland rice varieties as treatment used are  Inpago-4, Inpago- 5, Inpago- 6,  Situbagendit, Stone Tegi and local varieties as a comparison, each variety was repeated  4 times.  To determine the feasibility of technology to analyze revenue and cost  (B/C), while for  measuring the level of technological excellence  applied to farmers to use  marginal benefit cost ratio analysis (MBCR). The results showed that varieties Inpago 5 generate  the highest production (3.5 t/ha). The results of financial analysis shows Inpago-5 provide the highest  profits  with a gross value of B/C 2.18  and the marginal value of B / C of 4.69.. Based on the results of the study, varieties Inpago-5 is a decent variety of adaptive and developed by farmers.